And the Woman became Awake: The Figure of Rosa in the Comedy De tal siembra tal cosecha (1899) by Ángeles López de Ayala. Towards a new prototype of femininity at the crossroads of centuries XIX-XX - Martín-Clavijo, Milagro (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper analyzes the play De tal siembra tal cosecha (1889) by Ángeles López de Ayala, one of the most active and important freethinkers, republicans, and freemasons in Spain between the 19th and 20th centuries, and one of the most committed feminists of the time, both in theory and in practice. We study the elements that make the protagonist of the work a strong supporter of a different idea of feminine roles, yet without refusing to be mother and wife; she advocates an active role of women in their own emancipation from the family sphere and proposes a collaboration with men inside the couple relationship —accordingly with the thinking of the author and the articles published throughout her life.